Características que presenta la Ciudad Metropolitana de Trujillo – Región La Libertad, para el desarrollo del turismo urbano - Valderrama Rodríguez, Franklin Rousvelt (2022)
The present thesis called Characteristics presented by the Metropolitan City of Trujillo - La Libertad Region, for the development of urban tourism, had the purpose of identifying the characteristics presented by the metropolitan area of Trujillo to develop urban tourism, through its tourist attractions and plant tourist in operation._x000D_ From the great offer of tourist attractions that the metropolitan city of Trujillo has, seventeen had to be selected, taking into account their description, particularities, current state, access, distances, opening hours, permitted tourist activities, infrastructure, services, contribution urban tourism and its level of hierarchy; these are divided into three categories: natural sites, cultural manifestations and contemporary technical, scientific and artistic achievements. While, the tourist plant was characterized through the main types of company providing tourist services such as travel agencies, restaurant establishments and_x000D_ lodging establishments; From each of these, five companies were selected that stand out in quality of service, prestige, trajectory and installed capacity. Finally, it is verified that both as tourist attractions and tourist facilities, they comply with favorable characteristics that urban tourism requires._x000D_ During the development of this thesis, the following research methods were used: analytical – synthetic and ethnographic, which made it possible to break down the study variables into dimensions and allowed describing the characteristics that the metropolitan city of Trujillo presents for the development of urban tourism. The techniques used were: the signing, the observation and the interview with connoisseurs of tourist attractions and those in charge of the tourist plant. To this is added the instruments: data collection sheets, observation sheets, textual sheets, field notebook and cell phone.